Pengaruh Perilaku Konsumtif Dan Gaya Hidup Terhadap Keputusan Pembelian Skincare Somethinc (Studi Kasus Mahasiswi Feb Unidha Prodi S1 Manajemen) - Aisyah, Siti; Ezizwita (GLOBAL SCIENTS PUBLISHER, 2025)
This study is a quantitative study using a survey method. This study was conducted to determine the Influence of Consumtive Behavior and Lifestyle on Purchasing Decisions of Somethinc Skincare (Case Study of UNIDHA Undergraduate Manajemen Study Program Students). The study was conducted on female students of Dharma Andalas University. The population in the study was 348 people. Data was obtained through a questionnaire and the results of the analysis will be presented in table form. The sampling technique used non-probability sampling with a purposive sampling method with the criteria for respondents being active female students of Dharma Andalas University, who had purchased Somethinc Skincare products in the last 3 months. The sample size was calculated using the Rao Soft Sample Size Calculator software so that the sample in the study was 100 respondents. The results of the study showed that the variable Consumtive Behavior had a positive and significant effect on purchasing decisions, the variabel Lifestyle had a positive and significant effect on purchasing decisions, and the variables Consumtive Behavior and Lifestyle had a simultaneous effect on purchasing decisions.